2014
DOI: 10.9755/ejfa.v26i3.17385
|View full text |Cite
|
Sign up to set email alerts
|

Triazole compounds alters the antioxidant and osmoprotectant status in drought stressed Helianthus annuus L. plants

Abstract: A pot-culture experiment was conducted to estimate the ameliorating effect of triazole compounds Hexaconazole, Tebuconazole and Propiconazole on drought stress in sunflower (Helianthus annuus L.). The plants were subjected to drought (DID) stress after four days of interval from the 30th day of sowing (DAS). One-day-interval irrigation was kept as control. The plant samples were collected and separated into root, stem and leaf for estimating the amino acid (AA), proline (PRO) and glycine betaine (GB) contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Some agronomic measures can mitigate the damage of drought impact on plants, such as exogenous applications of plant hormones, osmotic regulators, and mineral nutrients (Salami and Saadat, 2013 ; Rabert et al, 2014 ). However, these changes are not heritable, and need additional labor, capital, and technology investment.…”
Section: Introductionmentioning
confidence: 99%
“…Some agronomic measures can mitigate the damage of drought impact on plants, such as exogenous applications of plant hormones, osmotic regulators, and mineral nutrients (Salami and Saadat, 2013 ; Rabert et al, 2014 ). However, these changes are not heritable, and need additional labor, capital, and technology investment.…”
Section: Introductionmentioning
confidence: 99%
“…Major environmental stresses such as drought, salinity and temperature impose a negative impact on plant's growth and development, ion uptake, primary and secondary metabolites, and oxidative system. Of them, drought is the most injurious one, because it markedly impairs growth and development of crops and their yield (Ashraf et al 2011, Rabert et al 2014, Akram et al 2016). Drought stress influences adversely the rate of photosynthesis, water transport and nutrition system, and formation of seeds (Aslam et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The triazol PGRs reduced transpiration, increased the relative water content, membrane stability, and significantly increased yield in wheat grown under water stress (Sairam et al, 1995). Rabert et al (2014) suggests the enhanced drought tolerance in triazoletreated plants is due to maintaining a balance between formation and detoxification of activated oxygen species, resulting in an improved response of plants to drought-induced oxidative stress. Sankar et al (2007) showed the adverse effects of water stress can be minimized with the application of PBZ, which increased the antioxidant levels and activities of scavenging enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…ater stress is one of the major abiotic stresses negatively affecting plant production and quality (Rabert et al, 2014). Plant responses to water stress involve either adaptive changes in metabolism and overall plant structure or deleterious effects such as reduced net photosynthesis and yield or leaf abscission (Durner, 2013;Vu et al, 2001).…”
mentioning
confidence: 99%